Ho Chi Minh's thought on Gender Equality in the Field of Politics in Vietnam - Trong Tha, Ha (International Journal of Psychosocial Rehabilitation, 2020)
President Ho Chi Minh (1890-1969) is a hero of national liberation and a preeminent cultural scholar of Vietnam. Throughout Ho Chi Minh's life, he always cared about humans and human rights, especially the equal rights of women in the field of politics. Gender equality in the field of politics is the core of equality between men and women and is the leading goal of the cause of human liberation. This article clarifies the basis of the formation and contents of Ho Chi Minh's thoughts on gender equality in the field of politics in Vietnam, emphasizing new and outstanding points in his thoughts. On that basis, the article states Vietnam's recent achievements in terms of gender equality in the field of politics. When applying Ho Chi Minh's thought on this issue, it is internationally regarded as a highlight of gender equality that many countries need to refer to.